Religion Sectarianism in Yoruba Land and Threats to Its Millennial Tribal Union - Matthew T. Taiwo; Victor O. Taiwo (Randwick International of Social Science Journal, 2020)
The Yoruba people have lived harmoniously as a kin for as long as the tribe has been in existence without religious strain despite the myriads of choices of beliefs that their traditional religion (Iseese) offered; and also, with the advent of foreign religions, Christian and Muslims have continuously live together in Yoruba land, often in harmony with practitioners of Yoruba traditional religion. In the recent age, there has been a curve of trend as the tribal relationships among the Yoruba people have gradually been eroding due to increasing infiltrations and activism of religion extremists. This research examined the damage religious sectarianism wreaked on the kinship relationship among the Yoruba folks. The research was qualitative, and situated within fundamentalism theory, a religious philosophy which depicts advocacy and strict adherence to a religious doctrine or belief. Data collections which are based on both primary and secondary sources are participatory, observatory and library oriented. It is concluded that religion has done more harm than good, but the situation can be redeemed with good understanding of the intended purpose of religion ingrained in the religious zealots.